2023
DOI: 10.1002/ijc.34575
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP9X loss sensitizes renal cancer cells to mTOR inhibition

Abstract: Mammalian target of rapamycin (mTOR) is a central regulator of mammalian metabolism and physiology. Aberrant hyperactivation of the mTOR pathway promotes tumor growth and metastasis, and can also promote tumor resistance to chemotherapy and cancer drugs; this makes mTOR an attractive cancer therapeutic target. mTOR inhibitors have been approved to treat cancer; however, the mechanisms underlying drug sensitivity remain poorly understood. Here, whole exome sequencing of three chromophobe renal cell carcinoma (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Solarek et al showed that insulin and insulin-like growth factors could serve as the intratumoral regulators of RC [ 39 ]. Roldán-Romero et al revealed that the loss of the deubiquitinase gene USP9X could sensitize RC cells to mTOR inhibition [ 40 ]. Nam et al shed light on that the TGF-β/HDAC7 pathway would suppress the metabolism of the TCA cycle in RC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solarek et al showed that insulin and insulin-like growth factors could serve as the intratumoral regulators of RC [ 39 ]. Roldán-Romero et al revealed that the loss of the deubiquitinase gene USP9X could sensitize RC cells to mTOR inhibition [ 40 ]. Nam et al shed light on that the TGF-β/HDAC7 pathway would suppress the metabolism of the TCA cycle in RC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%